The Narrative Analysis of the Discourse on Homosexual BDSM Pornograhic Video Clips of The Manhunt Variety - Milica Vasić (University of Belgrade, 2016)
In this paper we have analyzed the ideal-type model of the story which represents the basic framework of action in Manhunt category pornographic internet video clips, using narrative analysis methods of Claude Bremond. The results have shown that it is possible to apply the theoretical model to elements of visual and mass culture, with certain modifications and taking into account the wider context of the narrative itself. The narrative analysis indicated the significance of researching categories of pornography on the internet, because it leads to a deep analysis of the distribution of power in relations between the categories of heterosexual and homosexual within a virtual environment.